All my noble dreams and then what happens - Whelan, Gloria (Simon & Schuster Books for Young Readers, 2013)
As Rosalind continues to straddle the proper English world of her family and the culture of 1920s India where they live, her support of Gandhi and his followers in opposing British rule grows and she considers trying to carry the rebels' message to Edward, Prince of Wales, during his visit.